Pengembangan Tes Berpikir Kritis Akuntansi Terhadap Hasil Belajar Mahasiswa Akuntansi Universitas Dharmawangsa - Dewi Wahyuni; Mekar Meilisa Amalia (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This study aims to determine the ability of critical thinking accounting tests developed on accounting learning outcomes for students at Dharmawangsa University. The problem is focused on the critical thinking skills of 6th semester students in answering the test questions for management accounting courses. In order to approach this problem, Sugiyono's modified theoretical reference is used. The data were collected through four stages, namely design test, validation, limited trial and broad trial. The data were analyzed quantitatively using SPSS version 23 application tools. The data obtained were in the form of answers to the test questions given, containing critical thinking components, namely reason, inference, situation and clarity. This study concludes that the critical thinking skills of undergraduate accounting students at Dharmawangsa University are still not good. This is indicated by the average value of student respondents' results on the readability of critical thinking tests in the limited and broad trials obtained by 48.47% and 60.66%, respectively.